Anthropomorphous robot and kinematics model in general form - Phuc, Nguyen Thien (Vietnam Journal of Mechanics, 1995)
In this paper is represented a model of anthropomorphous robot with "the biomechanical pairs". This is the general received various kinds of robot, because from here can be received various kinds of robots as the particular cases. Accordingly, the kinematics model of the robot is also represented in general form. The proposed algorithm for solving inverse problem for the anthromorphous robot with n-degrees of freedom allows to receive analytical forms for the control parameters.